TO DIGITALIZE ENTERPRISE BUSINESS PROCESSES METHODOLOGICAL APPROACH - D. D. Suvanova (Web of Journals Publishing, 2023)
In this article, the classification of business processes from the point of view of digitization is carried out, the main tasks of digitization for each process and the systematization of the results expected from them, and the formation of the initial matrix of the introduction of digital technologies are discussed.
Keywords: business processes, digitization, digital technologies, classification, matrix.